Fabrication of Polylactide‐Based Biodegradable Thermoset Scaffolds for Tissue Engineering Applications. Issue 1 (7th May 2012) - Sakai, Reika; John, Baiju; Okamoto, Masami; Seppälä, Jukka V.; Vaithilingam, Jayasheelan; Hussein, Husnah; Goodridge, Ruth
Abstract The fabrication of tissue engineering scaffolds based on the polymerization of crosslinked polylactide using leaching and batch foaming to generate well‐controlled and interconnected biodegradable polymer scaffolds is reported. The scaffold fabrication parameters are studied in relation to the interpore connectivity, pore morphology, and structural stability of the crosslinked PLA scaffold. In vitro cell culture and in vitro degradation are used to analyze the biocompatibility and biodegradability of the scaffolds. The new crosslinked PLA thermoset scaffolds are highly suitable for bone tissue engineering applications due to their complex internal architecture, thermal stability, and biocompatibility. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>